Genetic diversity of bigeye thresher shark (Alopias superciliosus Lowe, 1841) landed in Palabuhanratu Fishing Port, Sukabumi, West Java, Indonesia - MEUTHIA MAHARANI KANEDI; DIAH PERMATA WIJAYANTI; ITA WIDOWATI; MUHAMMAD DANIE AL MALIK; NI LUH ASTRIA YUSMALINDA; ANDRIANUS SEMBIRING (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Kanedi MM, Wijayanti DP, Widowati I, Malik MDA, Yusmalinda NLA, Sembiring A. 2023. Genetic diversity of bigeye thresher shark (Alopias superciliosus Lowe, 1841) landed in Palabuhanratu Fishing Port, Sukabumi, West Java, Indonesia. Biodiversitas 24: 3488-3494. The bigeye thresher shark Alopias superciliosus (Lowe, 1841) is a highly migratory marine shark, widely distributed globally in tropical and temperate seas. The bigeye thresher shark is listed as a Vulnerable/VU species on the red list of the International Union for Conservation of Nature (IUCN) and listed on Appendix II of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Genetics is a substantial essential approach to conservation, management, and sustainability. This study investigates the bigeye thresher shark’s genetic diversity and structure populations A. superciliosus that landed in Palabuhanratu Fishing Port, Sukabumi, West Java, Indonesia. Samples were collected in Palabuhanratu (n=16) and secondary data from the Atlantic Ocean (n=212) and Indian Ocean (n=16) sequences were obtained from GenBank. A total of 16 sequences of A. superciliosus have been amplified using mitochondrial DNA control region (dloop) with 857 bp in size sequenced. The Genetic diversity result showed haplotype diversity value in Palabuhanratu (Hd=0.86667; ?=0.01048) considered a high value. Overall, AMOVA and FST results showed significant differences in population structure between Palabuhanratu, Atlantic, and Indian Ocean with an FST value of 0.04420 (p-value <0.05). Based on the result, an effective strategy is needed to manage A. superciliosus sharks, both with the government and the private sector.